Atom probe microscopy of zinc isotopic enrichment in ZnO nanorods - Ironside, Charlie; Saxey, David; Rickard, William; Gray, C.; McGlynn, E.; Reddy, Steven; Marks, Nigel (AIP Publishing LLC, 2017)
We report on atomic probe microscopy (APM) of isotopically enriched ZnO nanorods that measures the spatial distribution of zinc isotopes in sections of ZnO nanorods for natural abundance natZnO and 64Zn and 66Zn enriched ZnO nanorods. The results demonstrate that APM can accurately quantify isotopic abundances within these nanoscale structures. Therefore the atom probe microscope is a useful tool for characterizing Zn isotopic heterostructures in ZnO. Isotopic heterostructures have been proposed for controlling thermal conductivity and also, combined with neutron transmutation doping, they could be key to a novel technology for producing p-n junctions in ZnO thin films and nanorods. © 2017 Author(s).